Design and performance of passive solar compound parabolic concentrating collectors / Azizul Taat, Aizuddin Taat and Shahrul Annuar Harun - Taat, Azizul; Taat, Aizuddin; Harun, Shahrul Annuar (Faculty of Mechanical Engineering, 2003)
In our daily life, we need energy for living. We use energy for everything from cooking, to moving the vehicles until generating power plant. But it is getting less day by day. The energy source that we using like firewood, charcoal, petroleum, all are unrenewable, it will not last long instead we need to find it more as the use of it is increase. But if is also not clean and exhaustible that can contribute pollution to the world This project studies the performance of passive compound parabolic concentrating (CPC) solar collector under Malaysian climatic conditions. It involves the design of two types of CPC collectors, the hexagonal and the octagonal shapes, flie performances of these two collectors are then compared with two other established shapes, the sphere and the square The collector can collect both solar and daylight energy.